Iriarteeae palms tracked the uplift of Andean Cordilleras - Bacon, Christine D. (2018)
Aim: The high biodiversity of northern South America is unparalleled and includes several centres of diversity such as Amazonia, the Andes and the Choc o. Movement of lineages amongst and within these bioregions is thought to be rare, and the effect of those dispersals on the distribution, diversity, and community assembly remains poorly understood. Here we address these effects by studying divergence times, biogeographical history, and species diversification of the palm tribe Iriarteeae, an ecologically dominant forest component. Location: Central and South America. Methods: We developed a calibrated phylogeny and a spatially explicit diversification model that incorporates molecular and fossil data. In these analyses, we included a new fossil Iriartea species Gemmamonocolpites galeanoana, derived from new samples of Miocene deposits in western Amazonia. We also estimated the geographical range evolution of lineages and tested whether speciation and extinction rates were affected by dispersal events using a simulation approach in ClaSSE. Results: Dispersal amongst bioregions was not evenly distributed across the topology. We found that Amazonian communities are overdispersed across the phylogeny, whereas Andean taxa are clustered. Dispersal events were associated with increases in species diversification and were concomitant with periods of Andean uplift. Migration into montane areas occurred several times from lowland Amazonian ancestors, and montane taxa subsequently recolonized the Amazonian bioregion. Main conclusions: Our results suggest that the diversification of Iriarteeae palms closely followed the west-to-east surface uplift history of the Northern Andes. From an early, lowland Amazonian ancestor, the first diversification events took place in the earliest emerging mountain chain, the Western Cordillera. From there multiple range expansions followed eastwards and back into the lowlands. This study demonstrates how geological events within a single mountain range can affect the geographical expansion and diversification of lineages.